VD_FINDINFO HC / 2014 / 850 vom 10. September 2014 - VD Tribunal cantonal (2014)
RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL, INDEMNITÉEN GÉNÉRAL, DROIT AU SALAIRE | 337 CO, 337c al. 1 CO, 337c al. 3 CO